2006
DOI: 10.1088/0953-8984/18/45/010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ferromagnetism by nickel doping in the ‘112’ cobaltite EuBaCo2O5.50

Abstract: The study of the ordered oxygen deficient perovskite EuBaCo 2-x Ni x O 5.50 shows that the doping of cobalt sites by nickel induces a strong ferromagnetic component at low temperature in the antiferromagnetic matrix of EuBaCo 2 O 5.50 . This system exhibits indeed phase separation, i.e. consists of ferromagnetic domains embedded in the antiferromagnetic matrix of EuBaCo 2 O 5.50 . Besides, a magnetic transition is observed for the first time at 40K in the undoped and nickel doped phases, which can be attribute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
2
3
0
1
Order By: Relevance
“…1c) could be related to the ordering of the Sm 3+ moments. Similar type of ordering in the Eu sample has been reported by Raveau et al [30]. However, such ordering has disappeared in the Ca-doped samples, which could be related to the destruction of the magnetic ordering by substitution with non-magnetic calcium ions.…”
Section: Resultssupporting
confidence: 85%
“…1c) could be related to the ordering of the Sm 3+ moments. Similar type of ordering in the Eu sample has been reported by Raveau et al [30]. However, such ordering has disappeared in the Ca-doped samples, which could be related to the destruction of the magnetic ordering by substitution with non-magnetic calcium ions.…”
Section: Resultssupporting
confidence: 85%
“…Phenomena like double hysteresis and multiple steps in M vs. H curves were found in doped cobaltites Ga 1 À x Ca x BaCo 2 O 5.5 [28] and EuBaCo 2 À x M x O 5.5 with M 2 þ ¼ Zn 2 þ , Cu 2 þ [29] and M 2 þ ¼Ni 2 þ [30]. In undoped samples all cobalt ions are Co 3 þ , and the replacement of Ga 3 þ for Ca 2 þ in the first case and Co 3 þ for Zn 2 þ , Cu 2 þ or Ni 2 þ in the second case produce the oxidation of some amount of Co 3 þ to Co 4 þ .…”
Section: Magnetic Characterizationmentioning
confidence: 96%
“…They suggest the formation of superparamagnetic clusters within the antiferromagnetic matrix below 40 K, which are associated with the IS Co 3+ species. Moreover, it was reported that the substitution of Ni for Co enhances significantly the ferromagnetism in the Eu-phase (Raveau et al 2006b). More interestingly, ultrasharp magnetization multisteps were observed in these doped systems (figure 11), which were explained by the pinning effect of the Zn 2+ and Cu 2+ cations at the narrow domain walls of the ferromagnetic phase (Raveau et al 2006a).…”
Section: Magnetism: Complex Magnetic Transitions and Crucial Effect Omentioning
confidence: 88%
“…Such multisteps, observed in EuBaCo 1⋅85 Ni 0⋅15 O 5⋅57 below 5 K, were attributed to the domain-wall motion in a 'strong pinning' ferromagnetic system, which is very different from any metamagnetic transition previously observed in manganites. The Ni 2+ species change the local crystal field dramatically and induce a very effective pinning of the narrow domain walls at low temperature, responsible for the very sharp and large steps observed for the oxide EuBaCo 1⋅85 Ni 0⋅15 O 5⋅57 (Raveau et al 2006b).…”
Section: Magnetism: Complex Magnetic Transitions and Crucial Effect Omentioning
confidence: 99%